Experimental Validation of a Best-Fit Model for Predicting Radio Wave Propagation through Vegetation - Imoize, A. L.; Otuokere, E. M.; Ajose, S. O.; Adegbenro, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In this study, a model for predicting radio wave propagation through vegetation at 900 and 1800MHz is proposed. An integrated model comprising of ground and foliage induced effects is evaluated with respect to experimental data obtained through drive test in and around a vegetation environment, using Test Mobile System (TEMS) investigation tools. Measured path loss was compared against predictions made by four empirical vegetation models. Results indicate that the European Cooperation in Science and Technology (COST) 235 model gives the best prediction and compare favourably with measured path loss in areas where vegetation is dominant. Although, this model showed the most accurate prediction of foliage loss in the investigated area, there is a need to modify it for enhanced signal prediction. The modified model was found to predict the measured path loss with Root Mean Square Errors (RMSEs) of 6.98dB and 10.00dB at 900 and 1800MHz, respectively. Overall, findings revealed that these RMSEs are within the acceptable range of up to 15.00dB, for quality signal prediction in related environments